MICROMILLING AS A METHOD OF TEXTURING Ni-Ti ALLOYS SURFACE FOR WETTABILITY MODIFICATION - BALYTSKA, NATALIIA; MELNYCHUK, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores the potential of micro-milling texturing as a method for modifying the wettability of Ni-Ti alloy surfaces. The Ni-Ti alloy is particularly well-suited for implant manufacturing due to its capacity for body deformation, high strength, and biocompatibility. The modification of biomaterial surfaces with targeted alterations to their wetting properties represents a valuable approach to influencing cellular behaviour and eliciting desired biological responses. In this article, the fundamental phenomena of wetting are delineated. The surface free energy and geometric structure of solid surfaces govern their wetting properties; hence, modifying either of these factors can effect a change in the wettability of the surface. For a surface with a given surface free energy, a change in surface topography is employed to regulate the wettability of the surface. The article under discussion herein sets out to explore the limitations of the known mathematical models for predicting the contact angle of a surface as applied to a surface textured by micromilling. The paper goes on to compare the advantages of micromilling with other technological methods of surface texturing with regard to influencing their wetting properties. The paper sets out to consider the reasons for the low machinability of Ni-Ti alloys and the technical difficulties of their micromilling. It identifies the most studied surface textures for modifying the wetting properties of biomedical alloy surfaces that can be produced by micromilling. A comprehensive review of the literature reveals that micromilling allows for the fabrication of durable microtextures of diverse shapes and sizes without significant thermal effects on the surface or alterations in the chemical composition of the surface layer. This is of particular significance for preserving the functional properties of Ni-Ti alloy, a material with a shape memory effect.